Work Life Balance Terhadap Kepuasan Kerja Karyawan: - Arifiani, Zefi Nafira; Anisah, Laelatul; Rifki, Prayuda Nur (Psikodinamika: Jurnal Literasi Psikologi, 2026)
Job satisfaction is an individual's feelings expressed regarding various aspects of his/her work environment. Factors influencing it include evaluation of the work itself, career advancement opportunities, interactions with colleagues, quality of supervision, and overall perceived comfort level. This study uses a quantitative correlational approach. Data collection in this study uses a Work-life balance scale and a job satisfaction scale. The independent variable is work-life balance and the dependent variable is job satisfaction. The sample in this study amounted to 70 subjects. The sample of this study was taken using total sampling. The results of this study state that there is a relationship between Work-life balance and job satisfaction in employees at PT X. The direction between the two variables is positive, which means that the higher the work-life balance, the higher the job satisfaction in employees. Employees who experience Work-life balance will feel a balance between work and life, thus creating a feeling of satisfaction in workers. When individuals are able to balance the demands of work and personal life, they tend to feel more satisfied with their work as a whole.